PERANAN KELOMPOK PETERNAK TERHADAP USAHA PENGEMBANGAN TERNAK ITIK DI KECAMATAN TONDANO BARAT KABUPATEN MINAHASA - Tinenta, Suzeth G; Lombogia, S O.B; Oley, F S; Tumewu, J M (ZOOTEC, 2017)
ABSTRACTÂ THE ROLE OF HOUSEHOLD FARMER GROUP ON DEVELOPMENT OF DUCK FARMING SYSTEM IN WEST TONDANO DISTRICT OF MINAHASA REGENCY. Development of animal husbandry was generally intended to improve the human welfare of rural community, mainly increasing the productivity their animal farming system. This effort was mainly done to fulfil the nutritional needs of the communities in rural areas. The animal farming system was changed from the traditional way of animal maintenance into the intensive maintenance, requiring better understanding and knowledge of raising ducks. This research was carried out at the village of Tuutu, West Tondano district of Minahasa regency involving duck household farmer group from January 10, 2017 â€“ 10 April 2017. This research was applied using qualitative research. Data were collected intentionally based on purposive Sampling method, collected from primary and secondary sources of data. Primary data were obtained through direct observation held by interviews with the respondents of duck household farmers applying questions that have been prepared and drawn up in accordance with the research objectives. Secondary data were obtained from existing records in the Office of the head of the local Office and BP3K related with this study. Results of the study showed that all duck household farmer groups at the village of Tuutu, West Tondano district of Minahasa Regency were playing role in development of duck household farming system in making decision, involving the group. These groups were including four groups of Masawa-Sawangan, Tougela, Esa Toroan Waya and Toubeke.Key word: Household farming group, duck farming system development, West Tondano districtÂ